Gulf Coast Resilience Coalition: An Evolved Collaborative Built on Shared Disaster Experiences, Response, and Future Preparedness. (6th November 2015) - Hansel, Tonya Cross; Osofsky, Howard J.; Langhinrichsen-Rohling, Jennifer; Speier, Anthony; Rehner, Tim; Osofsky, Joy D.; Rohrer, Glenn
Abstract: Objective: For close to a decade, the Gulf Coast of the United States has been in almost constant disaster recovery mode, and a number of lessons have been learned concerning disaster recovery and behavioral health. The purpose of this report was to describe the natural development of a Gulf Coast Resilience Coalition (GCRC). Methods: The GCRC methods began with state-specific recovery goals following Hurricane Katrina in 2005 and transitioned to a shared multistate and multidiscipline coalition. The coalition's effectiveness is demonstrated through continuation, procurement of funding to provide response services, and increased membership to ensure sustainability. Results: The coalition has enhanced response, recovery, and resilience by providing strategic plans for dissemination of knowledge; post-disaster surveillance and services; effective relationships and communication with local, state, and regional partners; disaster response informed by past experience; a network of professionals and community residents; and the ability to improve access to and efficiency of future behavioral health coordination through an organized response. Conclusions: The GCRC can not only improve readiness and response, but work toward a shared vision of improved overall mental and behavioral health and thus resilience, with beneficial implications for the Gulf South and other communities as well. ( Disaster Med Public Health Preparedness . 2015;9:657–665)